Advanced Location-Based Technologies and Services - Karimi, Hassan A. (Taylor & Francis, 2013)
Due to the rapid increase in the number of mobile device users worldwide, location-based services (LBSs) have become pervasive, and the demand for them will continue to grow. Exploring recent changes in the technology and its uses, Advanced Location-Based Technologies and Services takes an in-depth look at new and existing technologies, techniques,